Epileptic seizure prediction using successive variational mode decomposition and transformers deep learning network - Wu, Xiao; Zhang, Tinglin; Zhang, Limei; Qiao, Lishan (Frontiers in Neuroscience, 2022)
As one of the most common neurological disorders, epilepsy causes great physical and psychological damage to the patients. The long-term recurrent and unprovoked seizures make the prediction necessary. In this paper, a novel approach for epileptic seizure prediction based on successive variational mode decomposition (SVMD) and Transformers is proposed. SVMD is extended to multidimensional form for time-frequency analysis of multi-channel signals. It could adaptively extract common band-limited intrinsic modes among all channels on different time scales by solving a variational optimization problem. In the proposed seizure prediction method, data is firstly decomposed into multiple modes at different time scales by multivariate SVMD, and then irrelevant modes are removed for preprocessing. Finally, power spectrum of denoised data is input to a pre-trained Bidirectional Encoder Representations from Transformers (BERT) for prediction. The BERT could identify the mode information related to epileptic seizures in time-frequency domain. It shows fair prediction performance on an intracranial EEG dataset with the average sensitivity of 0.86 and FPR of 0.18/h.